The Regional Ice Prediction System (RIPS): verification of forecast sea ice concentration. (25th March 2015) - Lemieux, Jean‐François; Beaudoin, Christiane; Dupont, Frédéric; Roy, François; Smith, Gregory C.; Shlyaeva, Anna; Buehner, Mark; Caya, Alain; Chen, Jack; Carrieres, Tom; Pogson, Lynn; DeRepentigny, Patricia; et al.
Abstract : In recent years, the demand for improved environmental forecasts in the Arctic has intensified as maritime transport and offshore exploration increase. As a result, Canada has accepted responsibility for the preparation and issuing services for the new Arctic MET/NAV Areas XVII and XVIII. Environmental forecasts are being developed based on a new integrated Arctic marine prediction system. Here, we present the first phase of this initiative, a short‐term pan‐Arctic 1/12° resolution Regional Ice Prediction System (RIPS). RIPS is currently set to perform four 48 h forecasts per day. The RIPS forecast model (CICE 4.0) is forced by atmospheric forecasts from the Environment Canada regional deterministic prediction system. It is initialized with a 3D‐Var analysis of sea ice concentration and the ice velocity field and thickness distribution from the previous forecast. The other forcing (surface current) and initialization fields (mixed‐layer depth, sea surface temperature and salinity) come from the 1/4° resolution Global Ice Ocean Prediction System. Three verification methods for sea ice concentration are presented. Overall, verifications over a complete seasonal cycle (2011) against the Ice Mapping System ice extent product show that RIPS 48 h forecasts are better than persistence during the growth season while they have a lower skill than persistence during the melt period. A better representation of landfast ice, oceanic processes (wave–ice interactions, upwelling events, etc.) in the marginal ice zone and better initializing fields should lead to improved forecasts.